Case Report: Premature Ventricular Beats-Induced Chronic Cough and Cough Syncope - Hu, Yue; Hua, Wen; Li, Na; Huang, Huaqiong (Frontiers in Medicine, 2021)
Background: Chronic cough is a common complaint that in rare cases can be caused by premature ventricular beats (PVCs). Materials and Methods: In this report, we present the case of a healthy 44-year-old female who presented persistent cough and cough syncope that was attributed to PVCs. Results: The cough disappeared after radiofrequency ablation, and no recurrence of arrhythmia or cough was observed. Conclusion: PVCs should be considered a probable cause of chronic cough and cough syncope in differential diagnosis.